Decomposition and release of nutrients from leaf litter in rubber plantations - Mercykutty Joseph, Geetha Jose and (Journal of Plantation Crops, 2016)
Establishment of cover crop has been a standard scientific agronomic intervention in rubber (Hevea brasiliensis) plantations. Natural leaf fall in rubber plantations is an unaccounted phenomenon which also improves the physicochemical properties and biological activities of soil. A comparison of the decomposition of leaf litter from different sources in soil and the release of Â utrients from them has been attempted in this study through a field experiment. Studies indicated that the degradation and release of nutrients to the soil pool was mainly decided by the leaf chemistry and degradability of the litter. Rubber litter had its own edge over other leguminous cover crop litter, in providing a sustained release of potassium, calcium and magnesium owing to its slow and steady mineralization rate compared to cover crops. Higher content of nutrients was recorded in degraded litter in comparison to fresh sources. Legume cover crops are capable of enhancing the bacterial and fungal populations in soil compared to nonleguminous crops in rubber plantations.